2013
DOI: 10.1016/s0140-6736(12)61963-1
|View full text |Cite|
|
Sign up to set email alerts
|

Long-term effects of continuing adjuvant tamoxifen to 10 years versus stopping at 5 years after diagnosis of oestrogen receptor-positive breast cancer: ATLAS, a randomised trial

Abstract: SummaryBackgroundFor women with oestrogen receptor (ER)-positive early breast cancer, treatment with tamoxifen for 5 years substantially reduces the breast cancer mortality rate throughout the first 15 years after diagnosis. We aimed to assess the further effects of continuing tamoxifen to 10 years instead of stopping at 5 years.MethodsIn the worldwide Adjuvant Tamoxifen: Longer Against Shorter (ATLAS) trial, 12 894 women with early breast cancer who had completed 5 years of treatment with tamoxifen were rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
1,226
4
58

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,789 publications
(1,350 citation statements)
references
References 18 publications
19
1,226
4
58
Order By: Relevance
“…Those that tolerated EXE well on during the study may have continued EXE. Some probably got extended TAM after ATLAS was presented and published [18]. Some probably continued OFS, with or without an AI.…”
Section: The Analysis Ignored the Efficacy Of Endocrine Therapy Aftermentioning
confidence: 99%
See 2 more Smart Citations
“…Those that tolerated EXE well on during the study may have continued EXE. Some probably got extended TAM after ATLAS was presented and published [18]. Some probably continued OFS, with or without an AI.…”
Section: The Analysis Ignored the Efficacy Of Endocrine Therapy Aftermentioning
confidence: 99%
“…This treatment suffers from a paucity of data showing that further endocrine therapy is effective after 5 years of an AI. In contrast, we know that more TAM improves survival after 5 years of TAM [18,19], and an AI improves DFS after 5 years of TAM [9,17]. By the end of 2016, one study had been published [20] and 3 more had been presented at the 2016 San Antonio Breast Cancer symposium showing little or no benefit for extending AI therapy beyond 5 years except for continued suppression of new contralateral breast cancers [21][22][23].…”
Section: Little Benefit From Hormonal Therapy After Ai For 5 Yearsmentioning
confidence: 99%
See 1 more Smart Citation
“…In ER-positive disease, a 47% reduction in breast cancer recurrence occurred in years 0 to 4 and a 32% reduction for years 5 through 9, although this benefit is not apparent in ER-negative disease [63]. The general recommendation for tamoxifen use is 5 years after diagnosis, although, a recent study conducted by Davies et al [64] found continuing adjuvant tamoxifen for a total of 10 years, in comparison to stopping at 5 years, further reduced recurrence and mortality.…”
Section: Breast Cancermentioning
confidence: 99%
“…Impact of CYP2D*6 in the adjuvant treatment of breast cancer patients with tamoxifen of 5 years of Tamoxifen treatment vs none, suggest that 10 years of tamoxifen treatment can approximately halve breast cancer mortality during the second decade after diagnosis [1] .…”
Section: Topic Highlightmentioning
confidence: 99%